2005
DOI: 10.1002/art.21247
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standardized method of assessment of radiographs and radiographic change in juvenile idiopathic arthritis: Introduction of the Dijkstra composite score

Abstract: Objective. To evaluate the sensitivity to change of a newly developed radiologic assessment tool, the Dijkstra score, and to develop a numeric composite score and progressor classification scheme to apply in juvenile idiopathic arthritis (JIA) trials.Methods. A placebo-controlled trial of sulfasalazine (SSZ) in patients with oligoarticular-and polyarticular-onset JIA yielded the data for this study. Data were obtained from 418 sets of radiographs of the clinically involved and contralateral joints (at study en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 14 publications
1
21
0
1
Order By: Relevance
“…* The letters A through F correspond to the specific radiographs in Figure 4. Little information exists on the use of standardized scoring systems of joint radiographs in JIA (5)(6)(7)(8)(9)(10)(11). Recent studies have shown that the Poznanski method is a reliable and sensitive instrument for assessing radiographic progression in clinical and research settings and in therapeutic trials (6,7,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…* The letters A through F correspond to the specific radiographs in Figure 4. Little information exists on the use of standardized scoring systems of joint radiographs in JIA (5)(6)(7)(8)(9)(10)(11). Recent studies have shown that the Poznanski method is a reliable and sensitive instrument for assessing radiographic progression in clinical and research settings and in therapeutic trials (6,7,9).…”
Section: Discussionmentioning
confidence: 99%
“…A number of scoring systems are available to quantify radiographic changes in adults with rheumatoid arthritis (3,4). However, little information exists on standardized measurement of radiographic damage in the investigation of disease outcome in children with juvenile idiopathic arthritis (JIA) (5)(6)(7)(8)(9)(10)(11). Furthermore, the assessment of radiographic progression has never been included in controlled trials of second-line agents in JIA.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies describing radiological features of JIA found most CR changes in the hands (57%), knees (47%), ankles (27%) and feet (36%), with erosions mainly in hands (18%) and feet (25%) 56. The hands and feet were the area most likely to show CR damage progression at 6 months and 5 years 57 58…”
Section: Resultsmentioning
confidence: 92%
“…Radiation exposure is a potential risk. In the absence of data to support clear benefit, radiographs should be obtained by the pediatric rheumatologist only when history and physical examination raise clinical concern about joint damage or decline in function (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Do Not Routinely Perform Surveillance Joint Radiographs To Mmentioning
confidence: 99%